2017
DOI: 10.1002/elan.201600680
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Glucose Biosensor Based on Electrochemically Deposited Gold Nanoparticles Covered by Polypyrrole

Abstract: Graphite rod (GR) modified with electrochemicaly deposited gold nanoparticles (AuNPs) and adsorbed glucose oxidase (GOx) was used in amperometric glucose biosensor design. Enzymatic formation of polypyrrole (Ppy) on the surface of GOx/AuNPs/GR electrode was applied in order to improve analytical characteristics and stability of developed biosensor. The linear glucose detection range for Ppy/GOx/AuNPs/GR electrode was dependent on the duration of Ppy‐layer formation and the linear interval was extended up to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…Gold nanocorals and carbon nanotubes were used to make a new all-solid Li + ion-selective electrode. By means of chronopotentiometry and SEM characterization, it was found that the capacitance of the conductive layer increased by 1-2 orders of magnitude, the impedance decreased significantly, the response time was less than 15 s, and the Nernst slope reached 58.70 mV/decade [28]. The shape memory polymers, which demonstrated shape recovery capability at room temperature, are worthy and challenging to be discussed for the in-situ agricultural applications [29].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanocorals and carbon nanotubes were used to make a new all-solid Li + ion-selective electrode. By means of chronopotentiometry and SEM characterization, it was found that the capacitance of the conductive layer increased by 1-2 orders of magnitude, the impedance decreased significantly, the response time was less than 15 s, and the Nernst slope reached 58.70 mV/decade [28]. The shape memory polymers, which demonstrated shape recovery capability at room temperature, are worthy and challenging to be discussed for the in-situ agricultural applications [29].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have optimized the efficiency of electron transfer by increasing the number of active sites and the catalytic ability of immobilized enzyme on sensor surface [11][12][13][14]. One of the most promising methods is to modify the surface of bare electrodes by metal nanomaterials with high superficial area, excellent biocompatibility and catalytic properties [13][14][15][16]. It has been confirmed that the electrical and catalytic properties of electrodes can be restructured by changing the surface morphology of nanoparticles through controlling different depositional conditions, like potential, reaction time and formulation of electrolyte [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies employed contact adsorption and/or electrochemical deposition to co-immobilize redox enzymes, molecular relays, and metallic nanoparticles, yielding effective bioelectrocatalysis. [17][18][19][20] Frequently used are also redox active mediators which are graed onto and/or constitute repetitive monomeric units in polymer hydrogels. [21][22][23] While the surface concentration of the relaying species in such assemblies is relatively high, these systems are prone to diffusional limitations of the enzymatic substrates and their products, hindering the charge transport and affecting the performance of the electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%